Feasibility investigation of a novel geothermal-based integrated energy conversion system: Modified specific exergy costing (M-SPECO) method and optimization. (December 2021) - Cao, Yan; Dhahad, Hayder A.; Togun, Hussein; Hussen, Hasanen M.; Anqi, Ali E.; Farouk, Naeim; Issakhov, Alibek
Abstract: The current work proposes and investigates a novel multigeneration system (power, hydrogen, and energy) comprising a flash-binary geothermal power plant, a modified Kalian cycle, a low-temperature electrolyzer, and a reverse osmosis desalination setup. Indeed, the whole system has been devised regarding the multi-heat recovery technique and smart management of products through a structural modification. To emphasize the ability of the newly designed system in this work, the data of the Sabalan geothermal plant in Iran has been used as a case study. Subsequently, the feasibility of the proposed multigeneration system has been examined by the modified specific exergy costing (M-SPECO) method, characterizing the exergetic and cost aspects of the system. The M-SPECO method is recognized as an energy level-based cost scrutiny technique to evaluate energy conversion systems. Accordingly, the sensitivity study through single and dual parametric analyses has been implemented, wherein separator 1 pressure was the main parameter. Likewise, the non-dominated sorting genetic algorithm-II (NSGA-II) method has been applied to optimize the calculations and reveal the optimum conditions and results. In this way, the achieved optimum exergy efficiency of the system was calculated as 47.25%, followed by a value of 7.66 $/GJ for the modified overall unit cost of products. Highlights: Proposing a novel geothermal multi-generation system with multi-heat recovery. Employing the exergy and modified exergoeconomic analyses through a case study. Enhancing the exergy and cost outcomes using a multi-objective optimization. Considering dual parametric study for the sensitivity viewpoint. Achieving the optimum exergy efficiency and unit cost of 47.25% and 7.66 $/GJ.